1990
DOI: 10.3177/jnsv.36.supplementii_s147
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Binding Peptides from Dietary Proteins

Abstract: SummaryThe undigested high-molecular weight fraction (HMF) of soybean protein prepared after exhaustive digestion either by microbial proteases or by pepsin exerted a remarkable hypocholester olemic activity compared to the parent protein in rats fed cholesterol-enriched diets. HMF bound in vitro with bile salts and stimulated fecal excretion of both neutral and acidic steroids far more than did soybean protein. Extraction of HMF with methanol slightly decreased the activity, but the methanol soluble fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
3
17
1
3
Order By: Relevance
“…Sugano et al has shown that undigested high-molecular-weight peptides might effectively bind bile acids in the intestine and thereby increase fecal excretion of both neutral and acidic steroids, resulting in induction of the hypocholesterolemic effect. [7][8][9][10] Thus, high-molecular fraction in soybean peptides can modulate cholesterol metabolism through the stimulation of fecal steroid excretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugano et al has shown that undigested high-molecular-weight peptides might effectively bind bile acids in the intestine and thereby increase fecal excretion of both neutral and acidic steroids, resulting in induction of the hypocholesterolemic effect. [7][8][9][10] Thus, high-molecular fraction in soybean peptides can modulate cholesterol metabolism through the stimulation of fecal steroid excretion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that soybean peptides also have a hypocholesterolemic effect. [7][8][9][10] This is because the peptides contain a high-molecular-weight (undigested) fraction, which is responsible for the stimulation of fecal steroid excretion, [7][8][9][10] but the effects of soybean peptides containing a low-molecular-weight (digested) fraction on cholesterol metabolism are unclear. Also, no consistent results have been obtained for the effect of soybean peptides on triglyceride metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean peptides containing high-molecular-weight (undigested) peptide fractions, obtained through the digestion of soybean protein isolate (SPI), are believed to play an important role in the hypocholesterolemic effect of soybean proteins (6)(7)(8)(9). High-molecular-weight soybean peptides are responsible for bile acid-binding, which results in the stimulation of fecal steroid excretion (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The various mechanisms underlying the hypocholesterolemic action of soybean protein include the suppression of intestinal cholesterol absorption, promotion of fecal steroid excretion, and increases in the rate of low-density lipoprotein (LDL) receptor-mediated cholesterol removal (3)(4)(5)(6)(7)(8)(9)(10)(11). Soybean peptides containing high-molecular-weight (undigested) peptide fractions, obtained through the digestion of soybean protein isolate (SPI), are believed to play an important role in the hypocholesterolemic effect of soybean proteins (6)(7)(8)(9). High-molecular-weight soybean peptides are responsible for bile acid-binding, which results in the stimulation of fecal steroid excretion (6)(7)(8)(9).…”
mentioning
confidence: 99%